How Has the COVID-19 Crisis Affected the Academic Stress of University Students? The Role of Teachers and Students - de la Fuente, Jesús; Pachón-Basallo, Mónica; Santos, Flavia H.; Peralta-Sánchez, Francisco J.; González-Torres, María Carmen; Artuch-Garde, Raquel; Paoloni, Paola V.; Gaetha, Martha L. (Frontiers in Psychology, 2021)
The effects of the COVID-19 pandemic have required substantial adjustments in university teaching-learning processes. The aim of this study was to verify whether there were significant differences between the academic year of 2020 and the two preceding years in factors and symptoms and stress. A total of 642 university students (ages 18 to 25 years) participated by filling out validated self-reports during the months from March to August 2020. Using an ex post facto design, SEM analyses, simple and multiple ANOVAs were performed. Structural results showed that stress factors from the teaching process had predictive value for the learning process, for emotions and academic burnout, and male gender was a factor predicting negative emotion. Complementarily, inferential results revealed no significant effect of academic year, but did show an effect of gender on stress experiences during the pandemic. Aside from certain specific aspects, there was no significant global effect of the year 2020 on factors and symptoms of stress. The results showed that studying in the year of the COVID-19 outbreak did not have a significant effect in stress triggered by the teaching process. From these results, we draw implications for specific guidance interventions with university teachers and students.